2018
DOI: 10.1002/aenm.201801372
|View full text |Cite
|
Sign up to set email alerts
|

Electroless Plating of Highly Efficient Bifunctional Boride‐Based Electrodes toward Practical Overall Water Splitting

Abstract: Exploring highly‐efficient and low‐cost electrodes for both hydrogen and oxygen evolution reaction (HER and OER) is of primary importance to economical water splitting. Herein, a series of novel and robust bifunctional boride‐based electrodes are successfully fabricated using a versatile Et2NHBH3‐involved electroless plating (EP) approach via deposition of nonprecious boride‐based catalysts on various substrates. Owing to the unique binder‐free porous nodule structure induced by the hydrogen release EP reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 135 publications
(100 citation statements)
references
References 45 publications
1
96
0
Order By: Relevance
“…Recently, Mullins and co‐workers presented an excellent analysis of the degree of oxidation in metal chalcogenides, pnictides, and carbides during OER and summarized the various theories for their electrochemical activity. In case of metal borides as well, OER proceeds in a similar fashion by forming surface oxide/hydroxide species . Operando X‐ray absorption spectroscopy (XAS) studies on Ni x B showed that during OER, Ni–B core remains intact while the surface oxidation state changes from Ni 2+ to Ni 3+ ( Figure a,b), thus giving direct evidence of the formation of surface NiOOH layer.…”
Section: Origin Of Electrochemical Activity In Metal Boridesmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, Mullins and co‐workers presented an excellent analysis of the degree of oxidation in metal chalcogenides, pnictides, and carbides during OER and summarized the various theories for their electrochemical activity. In case of metal borides as well, OER proceeds in a similar fashion by forming surface oxide/hydroxide species . Operando X‐ray absorption spectroscopy (XAS) studies on Ni x B showed that during OER, Ni–B core remains intact while the surface oxidation state changes from Ni 2+ to Ni 3+ ( Figure a,b), thus giving direct evidence of the formation of surface NiOOH layer.…”
Section: Origin Of Electrochemical Activity In Metal Boridesmentioning
confidence: 96%
“…However, it must be noted that a catalyst loading of 12.3 mg cm −2 was used in this work, which is very high and hence cannot be justly compared to the standard reports. Similarly, Co–B was also deposited on Ni foam and Ni foil wherein formation of curved nanosheets with a thickness of a few nanometers was observed on surface of Co–B/Ni foam, while Co–B/Ni foil displayed a porous nodule‐like structure with large number of internal spaces. When tested in 1 m KOH, Co–B/Ni foam showed η 10 = 110 and 315 mV, for HER and OER, respectively.…”
Section: Strategies Adopted To Enhance the Performance Of Metal Boridesmentioning
confidence: 99%
“…[1][2][3][4][5] So far, Pt is regarded as the most effective catalyst for hydrogen evolution reaction (HER) in acidic media, because of its appropriate adsorption of H atoms. [1][2][3][4][5] So far, Pt is regarded as the most effective catalyst for hydrogen evolution reaction (HER) in acidic media, because of its appropriate adsorption of H atoms.…”
mentioning
confidence: 99%
“…A constant current of 10 mA cm −2 can be well maintained for 15 h, with bubbles continuously evolved and released from the surfaces of both electrodes (Figure b). The performance of Ni−B−O@Ni 3 B is superior to the Pt−C and IrO 2 couple for overall water splitting ,. This makes the Ni−B−O@Ni 3 B one of the best reported bifunctional catalysts among the transition metal borides ,.…”
Section: Resultsmentioning
confidence: 98%
“…The performance of Ni−B−O@Ni 3 B is superior to the Pt−C and IrO 2 couple for overall water splitting ,. This makes the Ni−B−O@Ni 3 B one of the best reported bifunctional catalysts among the transition metal borides ,. Thus, surface oxidization strategy may be used on the development of practical bifunctional metal boride electrodes for overall water splitting.…”
Section: Resultsmentioning
confidence: 99%